Pulmonary cryptococcosis in non-AIDS patients - ,Jin-Quan (2012)
OBJECTIVE: To investigate the clinical features, management, and prognosis of pulmonary cryptococcosis in non-acquired immunodeficiency syndrome (AIDS) patients. METHOD: 24 cases of pulmonary cryptococcosis with accurate pathological diagnosis were retrospectively studied. RESULTS: 15 male patients and nine female patients were diagnosed at the first affiliated hospital of Sun Yat-sen University from November 1999 to November 2011. The mean age at the time of diagnosis was 44.2 ± 11.3 years (range: 24 to 65 years). Among these patients, 13 had other comorbidities. 15 were symptomatic and the other nine were asymptomatic. The most common presenting symptoms were cough, chest tightness, expectoration, and fever. None had concurrent cryptococcal meningitis. The most frequent radiologic abnormalities on chest computed tomography (CT) scans were solitary or multiple pulmonary nodules, and masses or consolidations, and most lesions were located in the lower lobes. All patients had biopsies for the accurate diagnosis. Among the 24 patients, nine patients underwent surgical resections (eight had pneumonectomy via thoracotomy and one had a pneumonectomy via thoracoscopy). Five of the patients who underwent surgery also received antifungal drug therapy (fluconazole) for one to three months after the surgery. The other 15 only received antifungal drug therapy (fluconazole or voriconazole) for three to six months (five patients are still on therapy). The follow-up observation of 19 patients who had already finished their treatments lasted from two to 11 years, and there was no relapse, dissemination, or death in any of these patients. CONCLUSION: Non-AIDS patients with pulmonary cryptococcosis have a good prognosis with appropriate management.